The international exposure of the Canadian banking system - Christian Friedrich; Hanno Friedrich; Nick Lawrence; Javier Cortes Orihuela; Phoebe Tian (Bank of Canada, 2025)
Over the past decade, the six largest Canadian banks held an increasingly greater share of their assets and liabilities abroad, linking the Canadian banking system more closely to economic and financial developments elsewhere in the world. In 2023, the share of Canadian banks' foreign assets and liabilities amounted to around 50%, with foreign exposures even exceeding domestic ones for some balance sheet items and calculations. Using a combination of regulatory and commercial data sources, we document Canadian banks' foreign activities and provide an overview of potential vulnerabilities that may be associated with them. The following facts emerge: First, Canadian banks' foreign activities differ considerably from their domestic ones. While Canadian banks engage domestically mostly with real sector entities, such as households and non-financial corporations, their most common counterparties abroad are non-bank financial institutions (NBFIs). To the extent that NBFIs or their behaviours might be less known to Canadian banks-for example, because of information asymmetries- a considerable exposure to such entities could constitute a potential vulnerability. Second, Canadian banks have sizable foreign currency and foreign country exposure to the US dollar and the United States, but also notable exposures to other currencies and countries. Third, we document the presence of an indirect foreign exposure channel for Canadian banks through lending to internationally exposed firms, even if these firms are domiciled in Canada and borrow in Canadian dollars. Lastly, we present a case study highlighting how Canadian banks have expanded internationally at times when banks of many other countries retreated.
Keywords: F21; F23; F31; F32; G21; G23; G3; 330; Financial institutions; International financial markets; Financial stability; International topics